2008
DOI: 10.1097/wno.0b013e3181782e52
|View full text |Cite
|
Sign up to set email alerts
|

Juxtapapillary Cytomegalovirus Retinitis With Optic Neuritis

Abstract: A 49-year-old man with AIDS developed acute monocular visual loss and an ipsilateral swollen optic disc with a large right relative afferent pupillary defect, a nerve fiber bundle visual field defect, and a peripapillary retinal infiltrate. Lumbar puncture disclosed cytomegalovirus (CMV) DNA on polymerase chain reaction (PCR). Treatment with oral valganciclovir produced complete resolution of the visual deficits and the fundus abnormality. This case differs from previously reported cases of CMV optic neuritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Several cases of CMV optic neuropathy in immune-compromised patients unrelated to CMV retinitis have also been described, including isolated optic neuritis, retrobulbar optic neuritis associated with meningoencephalitis and bilateral PORN, and bilateral retrobulbar optic neuritis following haploidentical hematopoietic stem cell transplantation 3135. A few cases of bilateral CMV papillitis without associated retinitis have been reported in young immunocompetent patients, with good recovery after antiviral therapy with or without associated corticosteroid therapy 3638.…”
Section: Viral Optic Neuropathiesmentioning
confidence: 99%
“…Several cases of CMV optic neuropathy in immune-compromised patients unrelated to CMV retinitis have also been described, including isolated optic neuritis, retrobulbar optic neuritis associated with meningoencephalitis and bilateral PORN, and bilateral retrobulbar optic neuritis following haploidentical hematopoietic stem cell transplantation 3135. A few cases of bilateral CMV papillitis without associated retinitis have been reported in young immunocompetent patients, with good recovery after antiviral therapy with or without associated corticosteroid therapy 3638.…”
Section: Viral Optic Neuropathiesmentioning
confidence: 99%
“…60 Treatment includes high doses of intravenous foscarnet and/or gancyclovir 63 and also with oral valgancyclovir. 64 Treatment should be initiated early before the development of optic atrophy.…”
Section: Infectious Optic Neuropathymentioning
confidence: 99%
“…At the end of this study, 65% of patients would have preferred to receive postoperative ocular protection. 4 Another study 5 also reported that patching could modulate inflammation and aid in wound healing.…”
Section: R Agrawalmentioning
confidence: 99%
“…CMV affects the optic nerve from an adjacent focus of peripapillary CMV retinitis and, concomitantly, peripheral foci of CMV retinitis may be noted. 4,5 Oral valganciclovir has proven to be a new and highly efficacious alternative to the chronic administration of ganciclovir in patients with CMV retinitis. In addition to its excellent bioavailability and favourable pharmacokinetic profile, valganciclovir has also proved to be cost effective and is the most widely used drug in the armamentarium for the treatment of CMV retinitis.…”
mentioning
confidence: 99%
See 1 more Smart Citation